Heat transfer and mass transfer in simulated solar-heated membrane distillation - Fernandez, Benedicto A.
Membrane Distillation (MD) is a relatively new separation method to process aqueous solutions. It has a great potential because of its low operating temperature and pressure, its high rejection rate of non-volatile solutes in the permeate solution and its ability to keep the resulting concentrated feed solution free from chemical degradation associated with intense heat.
MD involves simultaneous heat transfer and mass transfer through the membrane. The study analyzed the transport processes in a Direct-Contact MD (DCMD) set-up using a membrane module consisting of a flat channel test cell, a spacer and a Polyvinylidene flouride (PVDF) membrane.
The study was carried out in three aspects: The first aspect was experimental, where the effect of selected physical parameters on the heat and mass transport processes was examined. Experimental conditions simulated solar-heating of the feed, i.e., low-temperature heating and with only 10˚C of difference between the temperature of the feed and permeate solutions. The second aspect involved the use of some experimental data to solve the heat and mass transport coefficients, employing an analytical solution. The third aspect was a theoretical method, using equations derived from models to solve the same transport coefficients. This thrid aspect involved an iterative method, solved with the aid of a computer software.
The experimental results showed that the mass flux is directly proportional to three parameters: the mean bulk liquid temperature of the feed and parmeate, the recirculation rate of the feed and permeate, and the use of a coarse screen spacer in the membrane module. The analytical solutions revealed that the heat and mass transport processes are enhanced by the use of turbulent-promoting spacers. It also showed that the experimentset-up could be considered a well-designed one. The theoretical solution showed that simple diffusion (diffusion through a stagnant gas) is the dominant mechanism of mass transfer through the membrane. It also confirmed that the heat transfer through the membrane could be modeled validity by assuming constant heat of vaporization and constant vapor enthalpy.
By its results, simulated solar-heated MD was found to be a good alternative to the desalinating of sea water or brackish water in terms of mass flux and purity of water in the permeate. However, the volume of drinking water needed by a small community would already require a huge DCMD unit.
Thesis (MS Chemical Engineering)--University of the Philippines Diliman
Keywords: Separation (Technology); Distillation; Heat--Transmission.; Mass transfer; Membranes (Technology)